2019
DOI: 10.3348/kjr.2018.0541
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Inferior Capsular Laxity in Patients with Atraumatic Multidirectional Shoulder Instability with Magnetic Resonance Arthrography

Abstract: Objective To compare inferior capsular redundancy by using magnetic resonance arthrography (MRA) images in patients with multidirectional instability (MDI) of the shoulder and control subjects without instability and thereby develop a screening method to identify the presence of shoulder MDI. Materials and Methods The MRA images of patients with MDI of the shoulder (n = 65, 57 men, 8 women; mean age, 24.5 years; age range, 18–42 years) treated over an eight-year period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Magnetic resonance arthrography (MRA) either with saline or with contrast 77 has an advantage in this regard, as it is a more sensitive modality in detection of capsular laxity and redundancy (Figure 4). The particular finding on MRA for this pathology is J o u r n a l P r e -p r o o f an increase in the glenocapsular ratio, which is supportive of a diagnosis of hEDS 61 . In contrast to healthy patients with traumatic dislocations, the absence of a labral tear on cross-sectional imaging of an unstable shoulder is often more suggestive of a diagnosis of underlying hEDS.…”
Section: Diagnostic Imagingmentioning
confidence: 65%
“…Magnetic resonance arthrography (MRA) either with saline or with contrast 77 has an advantage in this regard, as it is a more sensitive modality in detection of capsular laxity and redundancy (Figure 4). The particular finding on MRA for this pathology is J o u r n a l P r e -p r o o f an increase in the glenocapsular ratio, which is supportive of a diagnosis of hEDS 61 . In contrast to healthy patients with traumatic dislocations, the absence of a labral tear on cross-sectional imaging of an unstable shoulder is often more suggestive of a diagnosis of underlying hEDS.…”
Section: Diagnostic Imagingmentioning
confidence: 65%
“…As inferior instability is the main component of MDI of the shoulder, previous authors experimented different methods to measure capsular redundancy, such as gleno-capsular ratio or labro-capsular distance and they all agree that increased axillary recess depth is correlated to shoulder instability [8,10]. Lee et al and Kim et al also found significant correlation between inferior capsular redundance and MDI [19,20].…”
Section: Discussionmentioning
confidence: 92%
“…Different methods have been previously reported; some authors have shown how an increased capsular volume, expressed as the three-dimensional capsular volume with respect to glenoid surface, and an increased sagittal cross-sectional capsular area are related to MDI [8,14]. However, they also observed that the glenoid surface area is not significantly different in patients with or without atraumatic instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies defined a symptomatic patient as a patient with pain alone ( 58 , 59 , 60 ), while eight studies accepted instability and/or subluxation and/or dislocation alone ( 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ). Twelve studies did not explicitly state what patient history would constitute a symptomatic patient ( 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ).…”
Section: Resultsmentioning
confidence: 99%